1998
DOI: 10.1002/(sici)1097-0290(19981220)60:6<712::aid-bit8>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the primary and secondary drying stages of the freeze drying of pharmaceutical products in vials: Numerical results obtained from the solution of a dynamic and spatially multi-dimensional lyophilization model for different operational policies

Abstract: A rigorous unsteady state and spatially multidimensional model is presented and solved to describe the dynamic behavior of the primary and secondary drying stages of the lyophilization of a pharmaceutical product in vials for different operational policies. The results in this work strongly motivate the aggressive control of freeze drying and it is found that heat input control that runs the process close to the melting and scorch temperature constraints yields (i) faster drying times, and (ii) more uniform di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(91 citation statements)
references
References 12 publications
5
81
0
5
Order By: Relevance
“…It has to be highlighted that in eq. (2) it has been assumed that product temperature is uniform i n t h e r a d i a l d i r e c t i o n , a s i t h a s b e e n demonstrated by means of mathematical simulation and experimental investigations (Pikal, 1985;Sheehan & Liapis, 1998). Various equations can be found in the literature to calculate the heat exchange coefficient K v in case the vial is placed directly over the shelf, i.e.…”
Section: Theoretical Calculation Of Heat Flux In Vial Freeze-dryingmentioning
confidence: 99%
“…It has to be highlighted that in eq. (2) it has been assumed that product temperature is uniform i n t h e r a d i a l d i r e c t i o n , a s i t h a s b e e n demonstrated by means of mathematical simulation and experimental investigations (Pikal, 1985;Sheehan & Liapis, 1998). Various equations can be found in the literature to calculate the heat exchange coefficient K v in case the vial is placed directly over the shelf, i.e.…”
Section: Theoretical Calculation Of Heat Flux In Vial Freeze-dryingmentioning
confidence: 99%
“…In most of the studies [19,20,22,25], the heat transfer by radiation from the door and walls of the drying chamber was considered completely responsible of the higher product temperature observed in edge vials. However, Gan et al [18] and Rambhatla et al [7] showed that the presence of the metallic rail surrounding vials also contributes to the heat transfer by means of contact conduction and radiation.…”
Section: Introductionmentioning
confidence: 96%
“…Several mono-and multi-dimensional mathematical models of freeze-drying were developed in the past years [16][17][18][19][20][21][22][23][24][25], but only few of them explore the sources of the atypical heat flow rate in edge vials. In most of the studies [19,20,22,25], the heat transfer by radiation from the door and walls of the drying chamber was considered completely responsible of the higher product temperature observed in edge vials.…”
Section: Introductionmentioning
confidence: 99%
“…VirTis freeze-drying system for PCR plates (vertical stripes), PCR plates with custom designed Al block (horizontal stripes), and 2R tubing vials (diagonal stripes). Graph plotted using data from (29) literature that describes the freeze-drying process (12,(31)(32)(33)(34)(35)(36)(37). There are differences between these models such as assumptions regarding the geometry of the ice sublimation interface, initial conditions, boundary conditions, and several other basic assumptions.…”
Section: Theoretical Modelingmentioning
confidence: 99%